Faktor Angin Pada Special-Effect Api Untuk Objek Bergerak Menggunakan Particle System - Farid Suryanto (SMATIKA JURNAL : STIKI Informatika Jurnal, 2019)
One technique in computer graphics that handles irregular objects with small size and is very large in number is a particle system. Particle systems are not only used to create fantasy effects but are also used to carry out simulations such as explosion simulations. One function of a particle system is to create a flame effect. The main variables for creating fire effects include start-delay, lifetime, speed, size, rotation, max-particle, emission-rate, shape-style, shape-angle, and shape-radius. Creating a flame effect that is influenced by wind factors on a moving object can be done by changing two parameters on the particle system, namely size and speed.